1990
DOI: 10.1063/1.346213
|View full text |Cite
|
Sign up to set email alerts
|

Structural investigation of silica gel films by infrared spectroscopy

Abstract: Fourier transform infrared absorption spectroscopy has been utilized to characterize the structure of porous silica gel films, both deposited on c-Si substrates and free standing. The films were either dried at room temperature or subjected to partial densification at 400–450 °C. The spectra of the gel films are compared to those of thermal SiO2 grown on c-Si and to Kramers–Kronig analysis of the reflection spectra of bulk SiO2 gels and v-SiO2. The gel films show small frequency shifts compared to the latter s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
226
0
10

Year Published

1998
1998
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 431 publications
(250 citation statements)
references
References 26 publications
14
226
0
10
Order By: Relevance
“…2. To the best of our knowledge, the band at $1300 cm À1 has never been observed on silica films and crystals [2,7,8,[23][24][25][26]. In addition, the band is by about 250 cm À1 higher than that of Si-O-Mo stretching vibrations on SiO 2 =Moð112Þ [2].…”
mentioning
confidence: 91%
“…2. To the best of our knowledge, the band at $1300 cm À1 has never been observed on silica films and crystals [2,7,8,[23][24][25][26]. In addition, the band is by about 250 cm À1 higher than that of Si-O-Mo stretching vibrations on SiO 2 =Moð112Þ [2].…”
mentioning
confidence: 91%
“…Furthermore, a diagnostic Si-O-Si asymmetric stretching vibration is centred on 1132 cm −1 [31,32] and the absorption signal at 920 cm −1 is assigned to the stretching vibration of silanol groups on the surface of the amorphous solid [33].…”
Section: Ftirmentioning
confidence: 99%
“…4 while Table 1 provides the IR peak assignments. 8,[23][24][25][26] It has previously been shown that above 300 °C, the hydrolysis of Si-N and Si-H bonds leads to the formation of a SiO 2 network. 8,[23][24] In the case of CAPS, the main absorption bands are observed at approximately 1180 cm -1 and 3360 cm -1 and correspond to the bend and stretch modes of N-H, respectively.…”
Section: Morphology and Chemistry Of The Gate Insulatormentioning
confidence: 99%